Difference between the Multiple Exemplar Instruction and Multiple Exemplar training: Literature review - Mascotti, Thais de Souza [UNESP]; Verdu, Ana Cláudia Moreira Almeida [UNESP] (My University, 2020)
The teaching with multiple exemplars of stimuli and of responses is well-established procedure in Behavior Analysis. Concepts of the Multiple Exemplar Training (MET) and of the Multiple Exemplar Instruction (MEI) has been adopted as equivalent, but they indicate, under some conditions, different arrangements. The present study reviewed the use of concepts of the MEI and of the MET in the literature; when the MEI was adopted, we evaluated the procedure arrangements have been used and their results. The literature review was conducted in September of 2018. The studies were selected in Web of Science, Scopus and Pubmed databases, without restriction of publication year. The search adopted the boolean descriptors and markers: *multiple*exemplar*instruction OR *multiple*exemplar*training*. These terms was exhibited in the topic in the Web of Science; in the title, the abstract or keyword in Scopus; and in the title or abstract in Pubmed. The search found 150 articles and 65 articles attended to inclusion criteria; duplicated papers, review and theorical articles, and studies with non-humans were excluded. The studies were analyzed by publication year and conceptual definition of the MEI or the of MET. When the MEI was adopted, we evaluated if it was the target or complementary procedure to proposed design. The taught operants, training structure, steps study, participants (number, age and diagnosis) and stimulus control of the MEI were analyzed. The number of stimuli set that were exposed until the participant attend to learning criteria in MEI were analyzed too. The results show that the MEI term is related to training structure that establishes the joint control of stimuli and the rotation between stimuli, responses or establishing operations. In some studies, the MET term refers to increase of exemplars of stimuli or of responses as generalization technology. In MEI that include rotative listening and speaking tasks, the exposure to a stimuli set is sufficient to produce speaking response in populations with different diagnosis; children with ASD are an exception and more sets can be require.
Diferenças entre o Ensino por Múltiplos Exemplares e o Treino por Múltiplos Exemplares: Revisão de literatura
Keywords: Literature review; Multiple exemplars; Stimulus control; Teaching; Verbal behavior